2021
DOI: 10.22207/jpam.15.2.02
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of COVID-19, Protective Measures and Attitude Towards Vaccination among University of Jeddah Health Field Community: A Questionnaire-Based Study

Abstract: This cross-sectional study aimed to measure the awareness, and attitude towards COVID-19 disease as well as new vaccine acceptance, among health field community (healthcare workers, health fields teaching staff and students) at the University of Jeddah, Jeddah Saudi Arabia. The questionnaire was designed in English language and included a set of 44 multiple-choice close-ended questions that covered demographic profile of participants, awareness of symptoms and practice against COVID-19. It also included a set … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 32 publications
1
14
0
Order By: Relevance
“…The results of included studies imply that generally, women hesitate more for getting vaccinated. Studies with a male percent of more than 40% reported a significantly higher rate of vaccine acceptability than most of the studies involving more women, 36–38 , 40–42 , 43 However, the intriguing point is that some exception studies that, despite involving more women, demonstrated a high rate of acceptability, 50 , 51 surprisingly sometimes even higher than other studies. 52 …”
Section: Discussionmentioning
confidence: 85%
See 4 more Smart Citations
“…The results of included studies imply that generally, women hesitate more for getting vaccinated. Studies with a male percent of more than 40% reported a significantly higher rate of vaccine acceptability than most of the studies involving more women, 36–38 , 40–42 , 43 However, the intriguing point is that some exception studies that, despite involving more women, demonstrated a high rate of acceptability, 50 , 51 surprisingly sometimes even higher than other studies. 52 …”
Section: Discussionmentioning
confidence: 85%
“…Males tended to have higher acceptability rates compared to the women, 36–38 , 40–43 Patients with underlying conditions that found themselves at higher risk of severe COVID-19 had better acceptability for the COVID-19 vaccines. 44 , Participants involved in healthcare services tend to have a higher vaccine acceptability rate compared to other groups.…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations